Biostratigraphy of large benthic foraminifera from the lower part of the Shahbazan Formation: revision of the age of the carbonate succession from the Tange Lilam section (Chenareh Anticline, Lorestan Basin) - Ali Reza Mohamadabadi; Mohamad Vahidinia; Meysam Shafiee Ardestani; Fateme Zabihi Zoeram (Journal of Stratigraphy and Sedimentology Researches, 2022)
AbstractIn this study, the lower part of carbonate successions from the Shahbazan Formation in the Chenareh anticline of the Zagros sedimentary basin (SW of Iran) based on Large Benthic Foraminifera (LBF) was investigated. From this succession, five species of Alveolina are described including A. fornasinii (Checchia-Rispoli), A. schwageri (Checchia-Rispoli), A. distefanoi (Checchia-Rispoli), A. cremaea (Checchia-Rispoli), A. decastroi (Scotto Di Carlo) along with species of Rotaliids such as Gyroidinella cf. magna (Le Calvez), Lockhartia hunti (Ovey), Cuvillierina vallensis (Ruiz De Gaona), Granorotalia sp. These assemblages of large foraminifera based on the Shallow Benthic Zones (SBZ) indicate the Late Ypresian (SBZ10–SBZ11). Thus, the detailed studies on this group of foraminifera were representative of the aforementioned age from the lower part of the Shahbazan Formation (Tang-e-Leilam section) for the first time. Therefore, identifying some species, such as Alveolina along with Rotaliids of the Early Eocene (Ypresian)succession was expressive of the Shahbazan Formation into the older time units. Keywords: Zagros sedimentary basin; Shahbazan Formation; Alveolina; Rotaliids.; Ypresian  IntroductionLBFs are the most ubiquitous marine benthic communities in the Eocene shallow-water carbonate successions of the Tethys domain. LBF studies have conspicuous potential to support the analysis of the biostratigraphic and paleobiogeographic interpretations during the Eocene. This paper deals with systematic research of some Alveolina, Somalina and Rotaliids species from the Shahbazan Formation in the Zagros region. Thereby, it is the first attempt on detailed taxonomic studies, while other investigations on the LBF assemblages have not been appropriately carried out so far from the Shahbazan Formation (e.g. Zabihi Zoeram et al. 2016. Abdolnia et al. 2017). On other words, the taxonomic identifications are not reliable, only based on random thin sections without providing appropriate sections on the LBF tests. About the Eocene LBF systematics of the Zagros region, aside from the reports of Rahaghi (1978, 1980, 1983) and Rahaghi and Schaub (1976), Only a few in-depth studies have recently been carried out on the Eocene LBF with precise stratigraphic records from the Jahrum Formation (e.g. Hottinger 2007; Hadi et al. 2019; Nafarieh et al. 2019a, b). Also, the age of the Shahbazan Formation based on the pioneer work of James and Wynd (1965) was assigned to the Middle-Upper Eocene in the type section. However, they did not illustrate the figures of zonal index markers with good preservation of LBF. Our main objective of this paper is to study the rotaliids and alveolinids systematics in the lower parts of the Shahbazan Formation with the description of the new larger porcellaneous Somalina shahbazensis n. sp.Material & MethodsThe Tang-e-Leilam section (Chenareh anticline), where the Shahbazan Formation has been measured, is located near (~10 km NE) the Cham-Gaz village, 35 km Pol-Dokhtar–Andimeshk road, and 100 km southwest Khoram-Abad. The coordinate of this outcrop section at the base is N 32˚, 59′, 02″ and E 47˚, 51′, 57″. Here, the Shahbazan Formation shows a thickness of 234.5 m, including the lower unit that is composed of grey, medium-bedded limestones with intercalated dolomitic-limestone layers, while the middle and upper parts are characterized by yellow to brown, medium-thick bedded dolostones and limy dolostone layers. A total of 11 rock samples were collected from the lower part of the formation in the Tang-e-Leilam section, and about 50 thin sections we prepared from these samples. Oriented and random Alveolina sections have been digitally photographed under transmitted light and a binocular microscope (Olympus BX51). The Alveolina were identified according to the taxonomic concepts given after Hottinger (1960, 1974), Drobne (1977), and Sirel and Acar (2008). SBZ are from Serra-Kiel et al. (1998) and Papazzoni et al. (2017). All specimens from the Tang-e-Leilam section are reposited in the Department of Geology, Ferdowsi University of Mashhad. Discussion of Results & ConclusionsAs mentioned in this research, few studies have been done on the biostratigraphy of shallow sea foraminifera of the Shahbazan Formation from the Zagros region. The published information indicates that the marine sediments of the Shahbazan Formation were deposited in the Middle–Late Eocene (see reference in Zabihi Zoeram et al. 2016; Abdolnia et al. 2017; Maghfouri Moghadam and Taherpour Khalil Abad, 2013; Maghfouri Moghadam et al. 2022). Here, we tried to compare the LBF collection identified with the present work, which unfortunately was not possible due to the weakness of previous studies. So, we try to refer to some problems case by case, although it is beyond the scope of the present study. In this research, for the first time, LBF from the carbonate succession of the lower part of the Shahbazan Formation was studied in detail. The results of this research include the following: 1- The species identified in this study represent the Late Ypresian age and are equivalent to SBZ10–SBZ11 according to the SBZ introduced from the Western Tethys Basin (Europe, Mediterranean) by Serra-Kiel et al. 1998). 2- Indicative species of wide geographical distribution throughout the western Tethys basin, such as A. fornasinii, A. schwageri, A. cremaea, A. distefanoi, and A. decastroi were identified in the study section. 3- In this research, the presence of A. distefanoi from Iran and the Zagros region was identified for the first time. Based on mentioned fauna such as (Gyroidinella cf. magna (Le Calvez), Lockartia hunti (Ovey) Gyroidinella cf. magna (Le Calvez), Cuvillierina vallensis (Ruiz De Gaona), Lockhartia hunti (Ovey), Granorotalia sp.) which shown the Shahbazan Formation was deposit during the Late Ypresian. 4- Thus, based on the available data, it is suggested to revise the age of the lower part of the Shahbazan Formation. In addition, the results of this research show that the overall revision of the age of the Shahbazan Formation in the Zagros Basin requires further studies